Analysis of Online Learning and Student's Level of Understanding in Islamic Education Subjects - Imam Tabroni; Diaz Budiarti; Rini Purnama Sari (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
Online learning has the potential to make students unable to understand the material presented by the teacher. This study aims to see the relationship between online learning and students' understanding of Islamic education subjects. The method used is correlation using a quantitative approach. The number of samples is the same as the total population, which is 28. After testing the instrument and collecting data, followed by data analysis using product moment correlation, the results of the research are that there is a positive relationship between online learning and students' understanding of Islamic education subjects. The positive relationship between online learning and students' understanding of this subject is 0.386. This relationship is good even though there are other factors that affect students' understanding of this online learning process.